CRITICAL AND CREATIVE THINKING SKILLS IN ELEMENTARY SCHOOL MINIMUM COMPETENCY ASSESSMENT: LITERACY AND NUMERACY - Sarah Anida Putri; Nadiya Solastika Andhini; Indah Amalia Putri; Novi Yanthi; Wati Sukmawati (Jurnal Cakrawala Pendas, 2024)
The purpose of this research was to identifying the occurence of critical thinking and crrative thinking skills indicators in the instruments of AKM (Minimum Performance Assessment). This research used qualitative descriptive method using documentary study. The research results showed that the content of AKM instrument in both literacy and numeracy questions were dominated by critical thinking skills appearance, with the major indicators of making deductions and considerations toward deduction, which belonged to the aspect of making inference. This indicator is the ability to make conclusions. The distribution of critical thinking skills indicators on literacy questions was 42% and 67% on numeracy questions. Meanwhile, the emergence of creative thinking aspects in literacy questions reached 3% and 5% in numeracy questions.